Decoding the molecular cascade of embryonic-uterine modulators in pregnancy loss of PCOS mother- an "in vivo" study - Shivani Dhadhal; Laxmipriya Nampoothiri (BMC, 2022)
Abstract Background Polycystic ovary syndrome is associated with an increased rate of spontaneous abortion/early pregnancy loss and pups delivered to PCOS animals were abnormal. Currently, assisted reproductive technology has been used to help numerous infertile couples to have their babies. However, there is a low implantation rate after the transfer of embryos. Till now, it could not be concluded whether the reduced pregnancy rates observed were due to abnormal embryos or endometrial modification. Further, transgenic mouse models have been used to find out the molecular deficits behind early pregnancy complications. But, the deletion of crucial genes could lead to systemic deficiencies/embryonic lethality. Also, pregnancy is a complex process with overlapping expression patterns making it challenging to mimic their stage-specific role. Therefore, the motive of the current study was to investigate the probable molecular cascade to decipher the early pregnancy loss in the letrozole-induced PCOS mouse model. Methods PCOS was induced in mice by oral administration of letrozole daily for 21 days. Following, the pregnancy was established and animals were sacrificed on the day 6th of pregnancy. Animals were assessed for early pregnancy loss, hormonal profile, mRNA expression of steroid receptors (Ar, Pr, Esr1/2), decidualization markers (Hox10/11a), adhesion markers (Itgavb3, Itga4b1), matrix metalloproteinases and their endogenous inhibitor (Mmp2/9, Timp1/2) and key mediators of LIF/STAT pathway (Lif, Lifr, gp130, stat3) were analyzed in the embryo implanted region of the uterus. Morphological changes in ovaries and implanted regions of the uterus were assessed. Results Mice treated with letrozole demonstrated significant increases in testosterone levels along with a decline in progesterone levels as compared to control animals. PCOS animals also exhibited decreased fertility index and disrupted ovarian and embryo-containing uterus histopathology. Altered gene expression of the steroid receptors and reduced expression of Hox10a, integrins, Mmp9, Timp1/3, Gp130 & Stat3 was observed in the implanted region of the uterus of PCOS animals. Conclusion Our results reveal that majority of the molecular markers alteration in the establishment of early pregnancy could be due to the aberrant progesterone signaling in the embryonic-uterine tissue of PCOS animals, which further translates into poor fetal outcomes as observed in the current study and in several IVF patients.